2020
DOI: 10.1038/s41433-020-01174-6
|View full text |Cite
|
Sign up to set email alerts
|

An objective method of diagnosing hydroxychloroquine maculopathy

Abstract: Background: Hydroxychloroquine (HCQ) maculopathy is irreversible; primary prevention is done by regular monitoring. Guidelines of the Royal College of Ophthalmologists identify definite toxicity as having abnormal results of two screening tests, we present a quantitative method for interpreting these guidelines. Methods: We obtained ocular coherence tomography (OCT) scans of 100 patients who have been on HCQ for 5 years or more (patients) and 70 age-matched controls. Both groups had 10'2 visual field (VF) test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The SD-OCT showed ONL thinning in 2/8 ETDRS sectors (5/8 previously) in the right eye and 3/8 ETDRS sectors (4/8 previously) in the left eye, figure 3, 19 February 2021. This no longer reaches our threshold for a diagnosis of HCQ retinopathy 6. ETDRS sector 4 (outer temporal) remained abnormal on SD-OCT after YAG laser capsulotomy, but 10–2 VF sector 4 reverted to normal after YAG laser capsulotomy.…”
Section: Outcome and Follow-upmentioning
confidence: 81%
See 2 more Smart Citations
“…The SD-OCT showed ONL thinning in 2/8 ETDRS sectors (5/8 previously) in the right eye and 3/8 ETDRS sectors (4/8 previously) in the left eye, figure 3, 19 February 2021. This no longer reaches our threshold for a diagnosis of HCQ retinopathy 6. ETDRS sector 4 (outer temporal) remained abnormal on SD-OCT after YAG laser capsulotomy, but 10–2 VF sector 4 reverted to normal after YAG laser capsulotomy.…”
Section: Outcome and Follow-upmentioning
confidence: 81%
“…The 10–2 VF tests were reliable. Testing in the right eye showed 8/8 Early Treatment of Diabetic Retinopathy Study (ETDRS) sectors were below the normal threshold and 7/8 ETDRS sectors were below normal threshold in the left eye,6 figure 2. The SD-OCT revealed outer nuclear layer (ONL) thinning in 5/8 ETDRS sectors in the right eye and 4/8 ETDRS sectors in the left eye, figure 3 6.…”
Section: Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these point-to-point structure-function analyses in patients treated with HCQ, we identify multiple OCT-derived quantitative metrics that exhibit correlation with visual field sensitivity. Previous analyses of HCQ toxicity using the Early Treatment Diabetic Retinopathy Study (ETDRS) grid have identified OCT-derived metrics such as EZ loss, thickness measures such as TRT and ORT, and intensity-based measures such as MinI as being relevant and correlated to visual field mean deviations measured across the retina 6 , 21 or to the visual field sensitivity in the ETDRS subfield. 21 Our analyses build upon these results to resolve what aspects of structural change are driving retinal function in each tested location.…”
Section: Discussionmentioning
confidence: 99%
“…7e9 De Sisternes et al 8 showed with segmentation OCT topography that retinal thickness in hydroxychloroquine users generally remains stable until near the time when retinopathy becomes evident and that thinning associated with toxicity occurs primarily in the outer retina. Hasan et al 10 described a technique that combines quantitative data from OCT studies and 10-2 visual fields to identify patients with hydroxychloroquine maculopathy, but their approach compares one-time measurements to statistical norms, which vary widely. Recently, Marmor et al 11 performed a pilot study of patients followed until the appearance of conventional OCT and 10-2 signs of hydroxychloroquine retinopathy and showed that sequential macular thickness plots using routine Early Treatment Diabetic Retinopathy Study (ETDRS) data could identify an onset of rapid retinal thinning several years before the appearance of conventional signs of hydroxychloroquine retinopathy.…”
mentioning
confidence: 99%